Interaction between Accounting Standards and Monetary Policy: The Effect of SFAS 115 - Meder, Anthony A. (The Accounting Review, 2015)
ABSTRACT I examine the effect of marketable security holdings on monetary policy when those securities are classified under SFAS 115. Prior research has shown that loan growth is negatively related to monetary contractions, and that marketable security holdings mitigate that negative relationship. Those studies consider the securities in aggregate; I am the first to consider the securities classification in conjunction with monetary policy. I ask whether held-to-maturity securities, relative to non-held-to-maturity securities, are negatively related to loan growth. I find that the held-to-maturity securities are more negatively related to loan growth, relative to non-held-to-maturity securities. I also find that held-to-maturity securities are incrementally more negatively related to loan growth during monetary tightening, relative to non-tightening times. Finally, I find that both of these effects are stronger for small banks, relative to large banks. Given the findings, I conclude that held-to-maturity securities actually enhance, not mitigate, the effect of monetary tightening on bank lending.